2016
DOI: 10.1097/ede.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Douching, Talc Use, and Risk of Ovarian Cancer

Abstract: Background Douching was recently reported to be associated with elevated levels of urinary metabolites of endocrine disrupting phthalates, but there is no literature on douching in relation to ovarian cancer. Numerous case-control studies of genital talc use have reported an increased risk of ovarian cancer, but prospective cohort studies have not uniformly confirmed this association. Behavioral correlation between talc use and douching could produce confounding. Methods The Sister Study (2003–2009) enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…A prospective study that followed 61,576 post-menopausal women for 12.4 years, however, could not link talc use with OC risk [ 76 ]. The results were confirmed by another independent study which found douching, and not talc use, as a risk factor for OC [ 77 ]. A recent meta-analysis, however, confirmed risk of OC from genital talc use with a statistically significant risk of serous OC [ 78 ].…”
Section: Biological Basis Of Ovarian Cancer Health Disparitiessupporting
confidence: 72%
“…A prospective study that followed 61,576 post-menopausal women for 12.4 years, however, could not link talc use with OC risk [ 76 ]. The results were confirmed by another independent study which found douching, and not talc use, as a risk factor for OC [ 77 ]. A recent meta-analysis, however, confirmed risk of OC from genital talc use with a statistically significant risk of serous OC [ 78 ].…”
Section: Biological Basis Of Ovarian Cancer Health Disparitiessupporting
confidence: 72%
“…At least 32 epidemiologic studies have examined the relation between talcum powder usage and ovarian cancer. 20,3767 Twelve out of the 32 epidemiologic studies of talc and ovarian cancer incorporated the Cosmetic, Toiletry, and Fragrance Association’s claim that “cosmetic” talc has been free of asbestos since 1976. 3840,43,45,47,48,56,57,59,61,64 The association between asbestos inhalation and ovarian cancer was noted in 1949, again in 1960, 68,69 and again in 1982.…”
mentioning
confidence: 99%
“…Three of the investigations were planned as prospective cohort studies and talc exposure was only evaluated once; thus, the studies did not prospectively evaluate talc exposure over time. 56,59,67 Also, given that the induction period and latency for ovarian cancer is between 25 and 40 years, 67 none of the study cohorts had sufficient follow-up time. 56,59,64,67 Gertig et al (Nurses’ Health Study) stated that, “Our relatively short follow-up period may be inadequate to detect an association if the latency for development of ovarian cancer is more than 15 years.” 56 Ten years later, Gates et al updated the Nurses’ Health Study talc use results, comparing rates of ovarian cancer between two groups of talc users (>1 week to <1 week) and found a near null rate ratio of 1.06 (95% CI = 0.89, 1.28).…”
mentioning
confidence: 99%
See 2 more Smart Citations